Oxidative treatment of tetracycline via persulfate activation using cross-linked magnetic MnFe2O4@green mussel shell chitosan catalyst in a fixed-bed column reactor - Henry D. Villanueva; Marjorie V. Tampos; Ramon E. Mina; Marielle M. Baldivino; Lorenz E. Borromeo (Journal of Water Process Engineering, 2026)

Caatinga Overland Flow Hydraulics: How Shrubs in the Brazilian Semi-Arid Environment Interact with Overland Flow - Cicero Gomes dos Santos; Jose Ramon B. Cantalice; Guilherme Santiago M. Cantalice; Juliano P. Sena Sousa; Ailton Alves de Carvalho; Daniel Moura Silva (Environmental Processes, 2026)
Hydraulic implications occur when rainfall and overland flow move across the vegetative structure of the Caatinga, the shrubland native to Brazil’s semi-arid region, which is a climate change hotspot. Can the Caatinga structure’s effects on rain interception, along with water retention caused by hydraulic resistance, significantly increase water infiltration? How can overland flow at low Reynolds numbers be affected? Twelve simulated rain events were conducted in a Brazilian semi-arid watershed, focusing on these questions in a degraded Caatinga area also used for growing semi-arid crops. The entire Caatinga vegetation and litter reduced flow velocity by 55.24% and 60.55%, respectively, and increased hydraulic resistance by 68.64% and 61.18%, respectively, compared to bare soil conditions. Hydraulic resistance was governed by the Froude number, as shown by a very good exponential decay function with a very high coefficient of determination (R 2 = 0.9902). Caatinga’s structural vegetative elements, such as litter (fallen leaves on the soil surface), and the entire Caatinga structure increase hydraulic resistance, providing an efficient environmental protection against overland flow. Therefore, even under the stress conditions of the dry season, Caatinga, as part of the semi-arid ecosystem, remains alive and ecologically active, responding hydraulically to overland flow.

Adipokines and satiety hormones and incidence of Alzheimer’s disease and dementia in older adults: a nested case-control study - Álvaro Hernáez; Javier Hernando-Redondo; Juan J. Chillarón; Emilio Ros; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Ramon Estruch; Juan Timiraos; Marta H. Hernández; Raquel Cueto-Galán; Miquel Fiol; et al. (GeroScience, 2026)
Obesity is known to have an intricate relationship with the development of Alzheimer’s disease and dementia (mid-life obesity increases risk, whereas late-life adiposity may also have an effect). In this context, adipokines and satiety signals are suggested to play a role in late life, but their association with the incidence of these outcomes remains unclear. Our study aimed to assess whether five selected plasma adipokines and satiety hormones (leptin, ghrelin, resistin, adipsin, and fibroblast growth factor-21) were associated with incident Alzheimer’s disease and dementia in older adults at high cardiovascular risk in a nested case-control study within the PREDIMED trial (90 dementia cases [73 of which were Alzheimer’s disease], 156 controls). Participants were at high cardiovascular disease risk but free from dementia at baseline. Associations with biomarkers were assessed using multivariable conditional logistic regression. Higher resistin levels were associated with higher incidence of Alzheimer’s disease in the multivariable-adjusted model (per one SD increase: OR 1.56, 95% CI 1.02 to 2.38); additional adjustment for body mass index slightly attenuated the association (OR 1.52, 95% CI 0.99 to 2.34). Our findings should be replicated in larger prospective studies but suggest that, despite the complex association between anthropometric measures and the incidence of dementia, high levels of resistin were tentatively associated with greater odds of incident Alzheimer’s disease in older adults at high cardiovascular risk.

Comparison of human and canine atopic dermatitis transcriptome: A meta-analysis and review from a one health perspective - Yu Wang; Jillian M. Richmond; Ramon M. Almela (Research in Veterinary Science, 2026)

Enhanced middle-distillate production through integrated non-noble metal catalysis on Fischer-Tropsch synthesis - M. Amine Lwazzani; Andrés A. García Blanco; Martí Biset-Peiró; Elena Martín Morales; Joan Ramon Morante; Jordi Guilera (Chemical Engineering Journal, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Daily dissolved oxygen saturation patterns mediated by light and stream discharge in littoral regions of an oligotrophic mountain lake - Heili E. Lowman; Kelly Loria; Leon Katona; Jasmine Krause; Sudeep Chandra; Sally MacIntyre; John M. Melack; Ramon Naranjo; Joanna R. Blaszczak (Aquatic Sciences, 2026)

Under pressure: accounting for multiple human pressures outside and inside marine protected areas in the Skagerrak - Helene Frigstad; Jesper H. Andersen; Trine Bekkby; Linus Hammar; Ashley D. Hemraj; Dag O. Hessen; Tobias K. Mildenberger; Even Moland; Ciarán J. Murray; Helle M. Sommer; Andy Stock; Johanna M. Aarflot; et al. (Frontiers in Marine Science, 2026)
The combined effects of multiple pressures pose critical threats to marine ecosystems. As an initial spatial assessment of cumulative pressures in the Skagerrak, we mapped where multiple pressures coincided with sensitive habitats and species, combining recent spatial data sets on 20 pressures and 39 habitats and species. The spatial data were linked with sensitivity weights obtained with a novel partly data-driven method. We found major spatial variation in the risk of cumulative impacts, identifying areas with high human impact, termed hot spots (such as shallow areas in southern and eastern Skagerrak), and areas with low human impact, termed cold spots (such as the deeper parts of the Norwegian Trench). The dominating human pressures were 1) fishing activities, 2) climate change, 3) underwater noise, 4) input of contaminants, 5) light pollution and 6) input of nutrients. Analyses of human pressures within and outside 20 Marine Protected Areas (MPAs) indicated significantly reduced levels in nine MPAs; however, these reductions were limited (less than 15%). One MPA (Skagens Gren og Skagerrak, DK) had significantly higher total human pressure inside the protected area, while ten MPAs did not yield significant results. We therefore recommend that the conservation measures in MPAs in the region be critically addressed and human pressures mitigated, to reduce the potential negative impact of human activities.

Ecophysiological characterization of thermophilic anammox process: Impact of environmental conditions and wastewater constituents on the activity of a novel granular thermophilic anammox culture - Badri Narayan Ravikumar; José M. Carvajal-Arroyo; Mingsheng Jia; Ramon Ganigué (Water Research, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Identifying a sustainable operating window for seaweed aquaculture in the Global North: balancing expansion barriers and carrying capacity - Sophie J.I. Koch; Ramon Filgueira; Jóhanna Alberg; Dror L. Angel; Carrie J. Byron; Mariana Cerca; Leeann B. Ennis; Urd Grandorf Bak; Frank Kane; Jonne Kotta; Stefan Kraan; Myron Peck; et al. (Aquaculture, 2026)

Synergistic Experimental and Theoretical Studies on Pesticide Detection in River samples Using Faujasite-CTAB Modified Carbon Paste Electrode - Cybelle C. C. M. Barbosa; Barbara L. Ramos; Elivelton A. Ferreira; Rodrigo G. Amorim; Ramon S. da Silva; Rodrigo Della Noce; Adriana E. de Carvalho; Mendelssolm K. de Pietre (Water, Air, & Soil Pollution, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

A serological test based on mutated recombinant Fasciola hepatica cathepsin L protease for the diagnosis of equine fasciolosis - Philipp A. Kronenberg; Nathalie Fouché; Mary Sekiya; Pauline Liechti; Caroline F. Frey; Grace Mulcahy; Ramon M. Eichenberger (Veterinary Parasitology, 2025)

An overview of the potential of select edible Amazonian fruits and their applications in dairy products - Bianca Cristina R. de Oliveira; Carolina Pinto de Carvalho Martins; Maria Eduarda M. Soutelino; Ramon S. Rocha; Adriano G. Cruz; Eliane T. Mársico; Adriana Cristina O. Silva; Erick A. Esmerino (Critical Reviews in Food Science and Nutrition, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Granulation of a planktonic thermophilic anammox culture enables high rate nitrogen removal from warm nitrogen rich wastewater: A proof of concept - Badri Narayan Ravikumar; Mingsheng Jia; Charlotte Geleyn; Thomas De Beer; José M. Carvajal-Arroyo; Ramon Ganigué (Chemical Engineering Journal, 2025)

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

Dietary vitamin D intake and 2-year changes in cognitive function in older adults with overweight or obesity and metabolic syndrome - Héctor Vázquez-Lorente; Jiaqi Ni; Indira Paz-Graniel; Estefanía Toledo; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (GeroScience, 2025)
The protective role of dietary vitamin D intake on cognitive function is of interest, but evidence remains inconsistent. We aimed to evaluate the association between dietary vitamin D intake and 2-year cognitive changes in older adults at risk of cognitive decline. This longitudinal study comprised 5454 individuals (aged 55–75 years in men and 60–75 years in women) who exhibited overweight/obesity and metabolic syndrome. Data on dietary vitamin D intake was assessed using a validated 143-item food frequency questionnaire. Cognitive function was assessed through five composite scores derived from a comprehensive battery of eight neuropsychological tests, encompassing global cognitive function, general cognitive function, attention, executive function, and language domains. Multivariable-adjusted linear regression models were fitted to examine the association between energy-adjusted cumulative average dietary vitamin D intake over time and 2-year changes in cognitive function. After adjusting for multiple covariates, energy-adjusted cumulative average dietary vitamin D intake as a continuous variable was associated with greater 2-year improvements in global cognitive function ( β 1.18 × 10 −2 ; 95% CI 0.19 × 10 −2 to 2.17 × 10 −2 ), executive function ( β 1.12 × 10 −2 ; 95% CI 0.03 × 10 −2 to 2.21 × 10 −2 ), and language ( β 1.61 × 10 −2 ; 95% CI 0.43 × 10 −2 to 2.78 × 10 −2 ). Additionally, the higher cumulative average dietary vitamin D intake quartile was associated with an increase in global cognitive function ( β 7.10 × 10 −2 ; 95% CI 0.59 × 10 −2 to 13.6 × 10 −2 ), language ( β 7.07 × 10 −2 ; 95% CI − 0.52 × 10 −2 to 14.7 × 10 −2 ), and a lower decline in attention ( β 9.58 × 10 −2 ; 95% CI 1.60 × 10 −2 to 17.5 × 10 −2 ). A higher dietary vitamin D intake was associated with modest favorable changes in cognitive function and a reduced cognitive decline over a 2-year period. These findings highlight the need for further research to explore the potential benefits of boosting dietary vitamin D intake for cognitive health in older adults.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Comparative population genomics of manta rays has global implications for management - Emily Humble; Jane Hosegood; Gary Carvalho; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Amelia Armstrong; Ramon Bonfil; Mark Deakos; Daniel Fernando; Niv Froman; Lauren R. Peel; et al. (Molecular Ecology, 2025)
Understanding population connectivity and genetic diversity is of fundamental importance to conservation. However, in globally threatened marine megafauna, challenges remain due to their elusive nature and wide‐ranging distributions. As overexploitation continues to threaten biodiversity across the globe, such knowledge gaps compromise both the suitability and effectiveness of management actions. Here, we use a comparative framework to investigate genetic differentiation and diversity of manta rays, one of the most iconic yet vulnerable groups of elasmobranchs on the planet. Despite their recent divergence, we show how oceanic manta rays ( Mobula birostris ) display significantly higher heterozygosity than reef manta rays ( Mobula alfredi ) and that M. birostris populations display higher connectivity worldwide. Through inferring modes of colonization, we reveal how both contemporary and historical forces have likely influenced these patterns, with important implications for population management. Our findings highlight the potential for fisheries to disrupt population dynamics at both local and global scales and therefore have direct relevance for international conservation of marine species.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Impact of pre-exposure stress on the growth and viability of Lactobacillus acidophilus in regular, buriti pulp and orange byproduct fermented milk products - Juliana S. Graça; Marianna M. Furtado; Luísa Freire; Carolina A. Watanabe; Ramon S. Rocha; Anderson S. Sant’Ana (Food Microbiology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Ohmic pasteurization of probiotic chocolate dairy desserts and its quality attributes - Gabriela R.A. Silva; Wanessa P. da Silva; Elson R. Tavares Filho; Louise de A. Sobral; Carolina P.C. Martins; Benjamin Mahieu; Jonas T. Guimarães; Maria Carmela K.H. Duarte; Mônica M. Pagani; Ramon Silva; Monica Q. Freitas; Eliane T. Mársico; et al. (Food Research International, 2024)

Quantifying the influence of updated land use/land cover in simulating urban climate: A case study of Metro Manila, Philippines - Alyssa Gewell A. Llorin; Lyndon Mark P. Olaguera; Angela Monina T. Magnaye; Faye Abigail T. Cruz; Julie Mae B. Dado; Emilio C. Gozo; Xzann Garry Vincent M. Topacio; Sherdon Niño Y. Uy; James Bernard B. Simpas; Jose Ramon T. Villarin (Theoretical and Applied Climatology, 2024)

Enhancing the functionality of yogurt: Impact of exotic fruit pulps addition on probiotic viability and metabolites during processing and storage - Eliene P. R. Pereira; Beatriz M. Ferreira; Luísa Freire; Iramaia Angélica Neri-Numa; Jonas T. Guimarães; Ramon S. Rocha; Glaucia M. Pastore; Adriano G. Cruz; Anderson S. Sant’Ana (Food Research International, 2024)

A comprehensive review of the use of traditional and emerging technologies for attenuation of probiotics strains - Cássia P. Barros; Tatiana C. Pimentel; Ramon Silva; Beatriz M. Ferreira; Wanderson R. Silva; Marco Antônio P. Silva; Leandro P. Cappato; Pedro Henrique C. Félix; Elane S. Purdencio; Erick A. Esmerino; Eliane T. Marsico; Mônica Q. Freitas; et al. (Food Control, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Cardiac alterations induced by Heloderma horridum horridum venom in rats: An experimental study with ECG analysis using a linear regression algorithm - Karla Isabel Vazquez-Gonzalez; Alberto Ochoa-Brust; Alejandrina Rodriguez-Hernandez; Hugo Ventura-Cisneros; Gisela Jareth Lino-Lopez; Rafael Barbosa-Valdovinos; Armando Rodriguez-Vazquez; Oscar F. Vazquez-Vuelvas; Ramon A. Felix; Juana M. Jiménez-Vargas; Valery Melnikov; Laura Leticia Valdez-Velazquez (Toxicon, 2024)

Comparative analysis of the chloroplast genomes in abaca (Musa textilis Née) cultivars reveals low chloroplast genome variation - Rhosener Bhea L. Koh; Jose Ramon G. Planta; Jayson C. Asunto; Cris Francis C. Barbosa; Vermando M. Aquino; Leny C. Galvez (Genetic Resources and Crop Evolution, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

DeLIA: A Dependability Library for Iterative Applications applied to parallel geophysical problems - Carla Santana; Ramon C.F. Araújo; Idalmis Milian Sardina; Ítalo A.S. Assis; Tiago Barros; Calebe P. Bianchini; Antonio D. de S. Oliveira; João M. de Araújo; Hervé Chauris; Claude Tadonki; Samuel Xavier-de-Souza (Computers & Geosciences, 2024)

A novel in vitro high-content imaging assay for the prediction of drug-induced lung toxicity - Paul A. Fitzpatrick; Julia Johansson; Gareth Maglennon; Ian Wallace; Ramon Hendrickx; Marianna Stamou; Kinga Balogh Sivars; Susann Busch; Linnea Johansson; Natalie Van Zuydam; Kelley Patten; Per M. Åberg; et al. (Archives of Toxicology, 2024)
The development of inhaled drugs for respiratory diseases is frequently impacted by lung pathology in non-clinical safety studies. To enable design of novel candidate drugs with the right safety profile, predictive in vitro lung toxicity assays are required that can be applied during drug discovery for early hazard identification and mitigation. Here, we describe a novel high-content imaging-based screening assay that allows for quantification of the tight junction protein occludin in A549 cells, as a model for lung epithelial barrier integrity. We assessed a set of compounds with a known lung safety profile, defined by clinical safety or non-clinical in vivo toxicology data, and were able to correctly identify 9 of 10 compounds with a respiratory safety risk and 9 of 9 compounds without a respiratory safety risk (90% sensitivity, 100% specificity). The assay was sensitive at relevant compound concentrations to influence medicinal chemistry optimization programs and, with an accessible cell model in a 96-well plate format, short protocol and application of automated imaging analysis algorithms, this assay can be readily integrated in routine discovery safety screening to identify and mitigate respiratory toxicity early during drug discovery. Interestingly, when we applied physiologically-based pharmacokinetic (PBPK) modelling to predict epithelial lining fluid exposures of the respiratory tract after inhalation, we found a robust correlation between in vitro occludin assay data and lung pathology in vivo, suggesting the assay can inform translational risk assessment for inhaled small molecules.

Effect of a nutritional intervention based on an energy-reduced Mediterranean diet on environmental impact - Laura Álvarez-Álvarez; María Rubín-García; Facundo Vitelli-Storelli; Silvia García; Cristina Bouzas; Miguel Ángel Martínez-González; Dolores Corella; Jordi Salas-Salvadó; Mireia Malcampo; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Associations of plasma proteomics and age-related outcomes with brain age in a diverse cohort - Ramon Casanova; Keenan A. Walker; Jamie N. Justice; Andrea Anderson; Michael R. Duggan; Jenifer Cordon; Ryan T. Barnard; Lingyi Lu; Fang-Chi Hsu; Sanaz Sedaghat; Anna Prizment; Stephen B. Kritchevsky; et al. (GeroScience, 2024)
Machine learning models are increasingly being used to estimate “brain age” from neuroimaging data. The gap between chronological age and the estimated brain age gap (BAG) is potentially a measure of accelerated and resilient brain aging. Brain age calculated in this fashion has been shown to be associated with mortality, measures of physical function, health, and disease. Here, we estimate the BAG using a voxel-based elastic net regression approach, and then, we investigate its associations with mortality, cognitive status, and measures of health and disease in participants from Atherosclerosis Risk in Communities (ARIC) study who had a brain MRI at visit 5 of the study. Finally, we used the SOMAscan assay containing 4877 proteins to examine the proteomic associations with the MRI-defined BAG. Among N = 1849 participants (age, 76.4 (SD 5.6)), we found that increased values of BAG were strongly associated with increased mortality and increased severity of the cognitive status. Strong associations with mortality persisted when the analyses were performed in cognitively normal participants. In addition, it was strongly associated with BMI, diabetes, measures of physical function, hypertension, prevalent heart disease, and stroke. Finally, we found 33 proteins associated with BAG after a correction for multiple comparisons. The top proteins with positive associations to brain age were growth/differentiation factor 15 (GDF-15), Sushi, von Willebrand factor type A, EGF, and pentraxin domain-containing protein 1 (SEVP 1), matrilysin (MMP7), ADAMTS-like protein 2 (ADAMTS), and heat shock 70 kDa protein 1B (HSPA1B) while EGF-receptor (EGFR), mast/stem-cell-growth-factor-receptor (KIT), coagulation-factor-VII, and cGMP-dependent-protein-kinase-1 (PRKG1) were negatively associated to brain age. Several of these proteins were previously associated with dementia in ARIC. These results suggest that circulating proteins implicated in biological aging, cellular senescence, angiogenesis, and coagulation are associated with a neuroimaging measure of brain aging.

Age Prediction Using Resting-State Functional MRI - Jose Ramon Chang; Zai-Fu Yao; Shulan Hsieh; Torbjörn E. M. Nordling (Neuroinformatics, 2024)

Observed characteristics and seasonality of the diurnal patterns of precipitation over Metro Manila, Philippines - Lyndon Mark P. Olaguera; Alyssa Gewell A. Llorin; Angela Monina T. Magnaye; Faye Abigail T. Cruz; Jose Ramon T. Villarin; Xzann Garry Vincent M. Topacio (Theoretical and Applied Climatology, 2024)

Evaluation of the Treatment with Akkermansia muciniphila BAA-835 of Chemotherapy-induced Mucositis in Mice - Ramon O. Souza; Vivian C. Miranda; Mônica F. Quintanilha; Bruno Gallotti; Samantha R. M. Oliveira; Janayne L. Silva; Jacqueline I. Alvarez-Leite; Luís C. L. Jesus; Vasco Azevedo; Kátia D. Vital; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2024)

Lateral sediment connectivity by curve number and a proposed approach to soil erodibility at the watershed scale - Juliana Farias S. Moraes; Jose Ramon B. Cantalice; Vijay P. Singh; Victor C. Piscoya; Moacyr Cunha Filho; Sergio M. S. Guerra; Pablo Lourenco Ribeiro Almeida (CATENA, 2024)

Differential apicomplexan presence predicts thermal stress mortality in the Mediterranean coral Paramuricea clavata - Anthony M. Bonacolta; Jordi Miravall; Daniel Gómez‐Gras; Jean‐Baptiste Ledoux; Paula López‐Sendino; Joaquim Garrabou; Ramon Massana; Javier del Campo (Environmental Microbiology, 2024)
Paramuricea clavata is an ecosystem architect of the Mediterranean temperate reefs that is currently threatened by episodic mass mortality events related to global warming. The microbiome may play an active role in the thermal stress susceptibility of corals, potentially holding the answer as to why corals show differential sensitivity to heat stress. To investigate this, the prokaryotic and eukaryotic microbiome of P. clavata collected from around the Mediterranean was characterised before experimental heat stress to determine if its microbial composition influences the thermal response of the holobiont. We found that members of P. clavata's microeukaryotic community were significantly correlated with thermal stress sensitivity. Syndiniales from the Dino‐Group I Clade 1 were significantly enriched in thermally resistant corals, while the apicomplexan corallicolids were significantly enriched in thermally susceptible corals. We hypothesise that P. clavata mortality following heat stress may be caused by a shift from apparent commensalism to parasitism in the corallicolid‐coral host relationship driven by the added stress. Our results show the potential importance of corallicolids and the rest of the microeukaryotic community of corals to understanding thermal stress response in corals and provide a useful tool to guide conservation efforts and future research into coral‐associated microeukaryotes.

Balancing food production with climate change mitigation and biodiversity conservation in the Brazilian Amazon - Ramon Felipe Bicudo da Silva; James D.A. Millington; Andrés Viña; Yue Dou; Emilio Moran; Mateus Batistella; David M. Lapola; Jianguo Liu (Science of The Total Environment, 2023)

Effects of short-chain per- and polyfluoroalkyl substances (PFAS) on toxicologically relevant gene expression profiles in a liver-on-a-chip model - Megan E. Solan; Bennett Schackmuth; Erica D. Bruce; Sahar Pradhan; Christie M. Sayes; Ramon Lavado (Environmental Pollution, 2023)

Reduction of ethanol content in wine with an improved combination of yeast strains and process conditions - Andrea M. Guindal; Pilar Morales; Jordi Tronchoni; Ramon Gonzalez (Food Microbiology, 2023)

Using structure-from-motion to estimate cover crop biomass and characterize canopy structure - April M. Dobbs; Daniel Ginn; Søren Kelstrup Skovsen; Ramawatar Yadav; Prashant Jha; Muthukumar V. Bagavathiannan; Steven B. Mirsky; Chris S. Reberg-Horton; Ramon G. Leon (Field Crops Research, 2023)

Evaluation of a Functional Craft Wheat Beer Fermented with Saccharomyces cerevisiae UFMG A-905 to treat Salmonella Typhimurium infection in mice - Samantha R. M. Oliveira; Lara L. Campos; Maisa N. S. Amaral; Bruno Galotti; Mayra F. Ricci; Katia D. Vital; Ramon O. Souza; Ana Paula T. Uetanabaro; Mateus S. Junqueira; Andreia M. Silva; Simone O. A. Fernandes; Valbert N. Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2023)

Directed evolution of Saccharomyces cerevisiae for low volatile acidity during winemaking under aerobic conditions - Andrea M. Guindal; Ramon Gonzalez; Jordi Tronchoni; Jorik S. Roodink; Pilar Morales (Food Microbiology, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Review - Sporeforming probiotic bacteria: Characteristics, health benefits, and technological aspects for their applications in foods and beverages - Mariana B. Soares; Carine N. Almada; Eliene P.R. Pereira; Beatriz M. Ferreira; Celso F. Balthazar; Nasim Khorshidian; Ramon S. Rocha; Douglas Xavier-Santos; Adriano G. Cruz; C. Senaka Ranadheera; Amir M. Mortazavian; Andrea Gómez-Zavaglia; et al. (Trends in Food Science & Technology, 2023)

Evaluation of rainbow trout (Oncorhynchus mykiss) organotypic intestinal platforms: cellular responses after long-term exposure to in vitro digested feed - Nicole Verdile; Federica Camin; Marcelo A. Chacon; Rolando Pasquariello; Radmila Pavlovic; David Peggs; Ramon Fontanillas; Amos Tandler; Trond M. Kortner; Amir Bitan; Tiziana A. L. Brevini; Fulvio Gandolfi (Frontiers in Marine Science, 2023)
Reliable and predictive in vitro models would support the search for new raw materials that can improve current fish diets. We recently developed some rainbow trout (RT) intestinal cell-based organotypic platforms demonstrating that the platform type modulates the degree of cell differentiation achieved in vitro and here we studied whether such differentiation correlates with their response to a prolonged exposure to a diet rich in fish meal. We compared three options, seeding the RTpiMI and RTdiMI cell lines derived respectively from the proximal or the distal intestine on (1) the polyethylene terephthalate (PET) culture inserts ThinCert ™ (TC); (2) the TC coated with RT fibroblasts embedded within Matrigel ® (MMfb); and (3) the highly porous polystyrene scaffold Alvetex ™ also populated with fibroblasts (AV). Platforms have been exposed for 21 days to increasing concentrations of feed pellets digested in vitro by gastric and intestinal RT enzymes (IVD). Cells exposed to culture medium without IVD in each platform were used as controls. TEER values became significantly higher than their respective controls in most culture conditions. At the end of culture, epithelial cells formed multilayers irrespective of cell line or platforms if exposed to IVD, but not in the controls. This proliferative activity followed a dose-dependent pattern in the AV, did not vary in MMfb, and was highly variable in the TC. Moreover, IVD induced the formation of a few goblet-like cells characterized by rounded vacuoles. In parallel, alanine aminopeptidase activity completely disappeared in the MMfb, significantly decreased in the AV, but did not change in TC. These changes suggest a de-differentiation of the enterocytes and their partial differentiation towards the secretory lineages. Overall, the three platforms reacted differently to a pronged exposure to IVD: TC quenched most of the cell responses, MMfb generated overly sensitive reactions, while the AV react mostly in a dose-dependent manner possibly generating more physiological results.

Looking behind occlusions: A study on amodal segmentation for robust on-tree apple fruit size estimation - Jordi Gené-Mola; Mar Ferrer-Ferrer; Eduard Gregorio; Pieter M. Blok; Jochen Hemming; Josep-Ramon Morros; Joan R. Rosell-Polo; Verónica Vilaplana; Javier Ruiz-Hidalgo (Computers and Electronics in Agriculture, 2023)

Dietary intake of polychlorinated dibenzo-p-dioxins and furans, adiposity and obesity status. - Nadine Khoury; María Ángeles Martínez; Indira Paz-Graniel; Miguel Ángel Martínez-González; Dolores Corella; Olga Castañer; J. Alfredo Martínez; Ángel M. Alonso-Gómez; Julia Wärnberg; Jesús Vioque; Dora Romaguera; José López-Miranda; et al. (Environmental Research, 2023)

Bringing the Nature Futures Framework to life: creating a set of illustrative narratives of nature futures - América Paz Durán; Jan J. Kuiper; Ana Paula Dutra Aguiar; William W. L. Cheung; Mariteuw Chimère Diaw; Ghassen Halouani; Shizuka Hashimoto; Maria A. Gasalla; Garry D. Peterson; Machteld A. Schoolenberg; Rovshan Abbasov; Lilibeth A. Acosta; et al. (Sustainability Science, 2023)
To halt further destruction of the biosphere, most people and societies around the globe need to transform their relationships with nature. The internationally agreed vision under the Convention of Biological Diversity—Living in harmony with nature—is that “By 2050, biodiversity is valued, conserved, restored and wisely used, maintaining ecosystem services, sustaining a healthy planet and delivering benefits essential for all people”. In this context, there are a variety of debates between alternative perspectives on how to achieve this vision. Yet, scenarios and models that are able to explore these debates in the context of “living in harmony with nature” have not been widely developed. To address this gap, the Nature Futures Framework has been developed to catalyse the development of new scenarios and models that embrace a plurality of perspectives on desirable futures for nature and people. In this paper, members of the IPBES task force on scenarios and models provide an example of how the Nature Futures Framework can be implemented for the development of illustrative narratives representing a diversity of desirable nature futures: information that can be used to assess and develop scenarios and models whilst acknowledging the underpinning value perspectives on nature. Here, the term illustrative reflects the multiple ways in which desired nature futures can be captured by these narratives. In addition, to explore the interdependence between narratives, and therefore their potential to be translated into scenarios and models, the six narratives developed here were assessed around three areas of the transformative change debate, specifically, (1) land sparing vs. land sharing, (2) Half Earth vs. Whole Earth conservation, and (3) green growth vs. post-growth economic development. The paper concludes with an assessment of how the Nature Futures Framework could be used to assist in developing and articulating transformative pathways towards desirable nature futures.

The phylogenomics and evolutionary dynamics of the organellar genomes in carnivorous Utricularia and Genlisea species (Lentibulariaceae) - Saura R. Silva; Vitor F.O. Miranda; Todd P. Michael; Bartosz J. Płachno; Ramon G. Matos; Lubomir Adamec; Sergei L.K. Pond; Alexander G. Lucaci; Daniel G. Pinheiro; Alessandro M. Varani (Molecular Phylogenetics and Evolution, 2023)

Association of microbiota polyphenols with cardiovascular health in the context of a Mediterranean diet - Inés Domínguez-López; Camila Arancibia-Riveros; María Marhuenda-Muñoz; Anna Tresserra-Rimbau; Estefanía Toledo; Montserrat Fitó; Emilio Ros; Ramon Estruch; Rosa M. Lamuela-Raventós (Food Research International, 2023)

Is an MRI-derived anatomical measure of dementia risk also a measure of brain aging? - Ramon Casanova; Andrea M. Anderson; Ryan T. Barnard; Jamie N. Justice; Anna Kucharska-Newton; Beverly Gwen Windham; Priya Palta; Rebecca F. Gottesman; Thomas H. Mosley; Timothy M. Hughes; Lynne E. Wagenknecht; Stephen B. Kritchevsky (GeroScience, 2023)

Differential proteomics of Zika virus (ZIKV) infection reveals molecular changes potentially involved in immune system evasion by a Brazilian strain of ZIKV - Juliana M. Tatara; Rafael L. Rosa; Ana Paula M. Varela; Tais F. Teixeira; Patrícia Sesterheim; Anderson Gris; David Driemeier; Amanda N. S. Moraes; Markus Berger; Ramon D. Peña; Paulo M. Roehe; Diogo O. G. Souza; et al. (Archives of Virology, 2023)

Microbiota of healthy and bleached corals of the species Siderastrea stellata in response to river influx and seasonality in Brazilian northeast - Gustavo Vasconcelos Bastos Paulino; Ciro Ramon Félix; Francisca Andréa da Silva Oliveira; Cinta Gomez-Silvan; Vânia M. M. Melo; Gary L. Andersen; Melissa Fontes Landell (Environmental Science and Pollution Research, 2022)

Global beta diversity patterns of microbial communities in the surface and deep ocean - Ernesto Villarino; James R. Watson; Guillem Chust; A. John Woodill; Benjamin Klempay; Bror Jonsson; Josep M. Gasol; Ramiro Logares; Ramon Massana; Caterina R. Giner; Guillem Salazar; X. Anton Alvarez‐Salgado; et al. (Global Ecology and Biogeography, 2022)
Aim Dispersal and environmental gradients shape marine microbial communities, yet the relative importance of these factors across taxa with distinct sizes and dispersal capacity in different ocean layers is unknown. Here, we report a comparative analysis of surface and deep ocean microbial beta diversity and examine how these patterns are tied to oceanic distance and environmental gradients. Location Tropical and subtropical oceans (30°N–40°S). Time period 2010–2011. Major taxa studied Prokaryotes and picoeukaryotes (eukaryotes between 0.2 and 3 μm). Methods Beta diversity was calculated from metabarcoding data on prokaryotic and picoeukaryotic microbes collected during the Malaspina expedition across the tropical and subtropical oceans. Mantel correlations were used to determine the relative contribution of environment and oceanic distance driving community beta diversity. Results Mean community similarity across all sites for prokaryotes was 38.9% in the surface and 51.4% in the deep ocean, compared to mean similarity of 25.8 and 12.1% in the surface and deep ocean, respectively, for picoeukaryotes. Higher dispersal rates and smaller body sizes of prokaryotes relative to picoeukaryotes likely contributed to the significantly higher community similarity for prokaryotes compared with picoeukaryotes. The ecological mechanisms determining the biogeography of microbes varied across depth. In the surface ocean, the environmental differences in space were a more important factor driving microbial distribution compared with the oceanic distance, defined as the shortest path between two sites avoiding land. In the deep ocean, picoeukaryote communities were slightly more structured by the oceanic distance, while prokaryotes were shaped by the combined action of oceanic distance and environmental filtering. Main conclusions Horizontal gradients in microbial community assembly differed across ocean depths, as did mechanisms shaping them. In the deep ocean, the oceanic distance and environment played significant roles driving microbial spatial distribution, while in the surface the influence of the environment was stronger than oceanic distance.

Bixa orellana L. from northern Brazil: morphological analysis, phenolic content, antioxidant and antibacterial activities - Sônia do Socorro do C. Oliveira; Ramon Diego C. Araújo; Gabriel A. da Silva; Jorge H. Leitão; Silvia Andreia Bento da Silva Sousa; Luis P. Fonseca; José Carlos T. Carvalho; Patrick Cantuária; Lorane I. da S. Hage-Melim; Irlon M. Ferreira (Brazilian Journal of Botany, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Guidelines on reporting treatment conditions for emerging technologies in food processing - Vicente M. Gómez-López; Gianpiero Pataro; Brijesh Tiwari; Mario Gozzi; María Ángela A. Meireles; Shaojin Wang; Buenaventura Guamis; Zhongli Pan; Hosahalli Ramaswamy; Sudhir Sastry; Florent Kuntz; Patrick J. Cullen; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Predicting in vitro fertilization success in the Brazilian public health system: a machine learning approach - Nayara C. N. Barreto; Giulia Z. Castro; Ramon G. Pereira; Francisco A. N. Pereira; Fernando M. Reis; Wagner M. Junior; Ines K. D. Cavallo; Karina B. Gomes (Medical & Biological Engineering & Computing, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Hydraulic resistance to overland flow governed by Froude number on semi-arid hillslopes under shrubs and crops - Jose Ramon B. Cantalice; I. C. G. M. Dias; D. S. Andrade; F. M. Assis Filho; W. L. S. Souza; E. O. S. Nunes; S. M. S. Guerra; V. P. Silva Junior; L. Sartori; F. J. Freitas; D. M. Cavalcante; José Romualdo de Sousa Lima; et al. (Hydrological Sciences Journal, 2021)

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

Using fisher‐contributed secondary fins to fill critical shark‐fisheries data gaps - Jessica R. Quinlan; Shannon J. O'Leary; Andrew T. Fields; Martin Benavides; Emily Stumpf; Ramon Carcamo; Joel Cruz; Derrick Lewis; Beverly Wade; George Amato; Sergios‐Orestis Kolokotronis; Gina M. Clementi; et al. (Conservation Biology, 2021)
Developing‐world shark fisheries are typically not assessed or actively managed for sustainability; one fundamental obstacle is the lack of species and size‐composition catch data. We tested and implemented a new and potentially widely applicable approach for collecting these data: mandatory submission of low‐value secondary fins (anal fins) from landed sharks by fishers and use of the fins to reconstruct catch species and size. Visual and low‐cost genetic identification were used to determine species composition, and linear regression was applied to total length and anal fin base length for catch‐size reconstruction. We tested the feasibility of this approach in Belize, first in a local proof‐of‐concept study and then scaling it up to the national level for the 2017–2018 shark‐fishing season (1,786 fins analyzed). Sixteen species occurred in this fishery. The most common were the Caribbean reef ( Carcharhinus perezi ), blacktip ( C. limbatus ), sharpnose (Atlantic [ Rhizoprionodon terraenovae ] and Caribbean [ R. porosus ] considered as a group), and bonnethead ( Sphyrna cf. tiburo ). Sharpnose and bonnethead sharks were landed primarily above size at maturity, whereas Caribbean reef and blacktip sharks were primarily landed below size at maturity. Our approach proved effective in obtaining critical data for managing the shark fishery, and we suggest the tools developed as part of this program could be exported to other nations in this region and applied almost immediately if there were means to communicate with fishers and incentivize them to provide anal fins. Outside the tropical Western Atlantic, we recommend further investigation of the feasibility of sampling of secondary fins, including considerations of time, effort, and cost of species identification from these fins, what secondary fin type to use, and the means with which to communicate with fishers and incentivize participation. This program could be a model for collecting urgently needed data for developing‐world shark fisheries globally. Article impact statement : Shark fins collected from fishers yield data critical to shark fisheries management in developing nations.

Phylogenetic diversity and dominant ecological traits of freshwater Antarctic Chrysophyceae - Irina Izaguirre; Fernando Unrein; M. Romina Schiaffino; Enrique Lara; David Singer; Vanessa Balagué; Josep M. Gasol; Ramon Massana (Polar Biology, 2021)

Assessment of the Restoration of the Remolar Dune System (Viladecans, Barcelona): The Resilience of a Coastal Dune System - Antoni Calafat; Sara Vírseda; Raúl Lovera; Joan Ramon Lucena; Carme Bladé; Lluís Rivero; Josep M. Ninot (Journal of Marine Science and Engineering, 2021)
The Remolar beach-dune system (700 m long and more than 100 m wide, 070N direction) borders a campground that was closed (2003), due to the Barcelona airport expansion. In order to recover and restore the dune ecosystem, a series of soft measures were performed. After 10 years, a study of the morphology, sedimentology, and vegetation of the ecosystem was carried out to evaluate the results of these measures. For this purpose, a series of topographic and ground-penetrating radar (GPR) profiles, grain-size analysis, and an analysis of plant communities found along the profiles were carried out. The data obtained were compared with data from a former 2004 study. The results show that the morphology of the dunes recovered, and a new primary dune has arisen. The system now has a greater process of aggradation than of progradation. The vegetation has recovered the global composition of dune systems, with a typical community of embryo dunes and others of primary dunes that are set in strips parallel to the coast. Despite this improvement, the opportunistic and ruderal component in the primary dune vegetation evidences a strong anthropic inheritance in the system.

Phylogenomics and species delimitation for effective conservation of manta and devil rays - Jane Hosegood; Emily Humble; Rob Ogden; Mark de Bruyn; Simon Creer; Guy M. W. Stevens; Mohammed Abudaya; Kim Bassos‐Hull; Ramon Bonfil; Daniel Fernando; Andrew D. Foote; Helen Hipperson; et al. (Molecular Ecology, 2020)
Practical biodiversity conservation relies on delineation of biologically meaningful units. Manta and devil rays (Mobulidae) are threatened worldwide, yet morphological similarities and a succession of recent taxonomic changes impede the development of an effective conservation strategy. Here, we generate genome‐wide single nucleotide polymorphism (SNP) data from a geographically and taxonomically representative set of manta and devil ray samples to reconstruct phylogenetic relationships and evaluate species boundaries under the general lineage concept. We show that nominal species units supported by alternative data sources constitute independently evolving lineages, and find robust evidence for a putative new species of manta ray in the Gulf of Mexico. Additionally, we uncover substantial incomplete lineage sorting indicating that rapid speciation together with standing variation in ancestral populations has driven phylogenetic uncertainty within Mobulidae. Finally, we detect cryptic diversity in geographically distinct populations, demonstrating that management below the species level may be warranted in certain species. Overall, our study provides a framework for molecular genetic species delimitation that is relevant to wide‐ranging taxa of conservation concern, and highlights the potential for genomic data to support effective management, conservation and law enforcement strategies.

Plasma Vitellogenin Reveals Potential Seasonal Estrogenicity in Fish from On-Site Wastewater Treatment Systems in Semi-Arid Streams Influenced by Snowmelt - Marco E. Franco; Kevin M. Stroski; Jaylen L. Sims; S. Rebekah Burket; Craig Ashcroft; Michael Luers; Bryan W. Brooks; Ramon Lavado (Bulletin of Environmental Contamination and Toxicology, 2020)

Multilocus and morphological analysis of south‐eastern Iberian Wall lizards (Squamata, Podarcis ) - Marta Bassitta; Joana M. Buades; Ana Pérez‐Cembranos; Valentín Pérez‐Mellado; Barbara Terrasa; Richard P. Brown; Pilar Navarro; Javier Lluch; Jesús Ortega; Jose A. Castro; Antònia Picornell; Cori Ramon (Zoologica Scripta, 2020)
The phylogenetic relationships among the wall lizards of the Podarcis hispanicus complex that inhabit the south‐east (SE) of the Iberian Peninsula and other lineages of the complex remain unclear. In this study, four mitochondrial and two nuclear markers were used to study genetic relationships within this complex. The phylogenetic analyses based on mtDNA gene trees constructed with ML and BI, and a species tree using *BEAST support three divergent clades in this region: the Valencia, Galera and Albacete/Murcia lineages. These three lineages were also corroborated in species delimitation analyses based on mtDNA using bPTP, mPTP, GMYC, ABGD and BAPS. Bayesian inference species delimitation method (BPP) based on both nuclear data and a combined data set (mtDNA + nuclear) showed high posterior probabilities for these three SE lineages (≥0.94) and another Bayesian analysis (STACEY) based on combined data set recovered the same three groups in this region. Divergence time dating of the species tree provided an estimated divergence of the Galera lineage from the other SE group ( Podarcis vaucheri , (Albacete/Murcia, Valencia)) at 12.48 Ma. During this period, the Betic–Rifian arc was isolated, which could have caused the isolation of the Galera form distributed to the south of the Betic Corridor. Although lizards from the Albacete/Murcia and Galera lineage are morphologically similar, they clearly represent distinct genetic lineages. The noteworthy separation of the Galera lineage enables us to conclude that this lineage must be considered as a new full species.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Protecting the Cerrado: where should we direct efforts for the conservation of bat-plant interactions? - H. F. M. Oliveira; N. F. Camargo; Y. Gager; R. L. Muylaert; E. Ramon; R. C. C. Martins (Biodiversity and Conservation, 2019)

Assessing the viral content of uncultured picoeukaryotes in the global‐ocean by single cell genomics - Yaiza M. Castillo; Jean‐François Mangot; Luiz Felipe Benites; Ramiro Logares; Megumi Kuronishi; Hiroyuki Ogata; Olivier Jaillon; Ramon Massana; Marta Sebastián; Dolors Vaqué (Molecular Ecology, 2019)
Viruses are the most abundant biological entities on Earth and have fundamental ecological roles in controlling microbial communities. Yet, although their diversity is being increasingly explored, little is known about the extent of viral interactions with their protist hosts as most studies are limited to a few cultivated species. Here, we exploit the potential of single‐cell genomics to unveil viral associations in 65 individual cells of 11 essentially uncultured stramenopiles lineages sampled during the Tara Oceans expedition. We identified viral signals in 57% of the cells, covering nearly every lineage and with narrow host specificity signal. Only seven out of the 64 detected viruses displayed homologies to known viral sequences. A search for our viral sequences in global ocean metagenomes showed that they were preferentially found at the DCM and within the 0.2–3 µm size fraction. Some of the viral signals were widely distributed, while others geographically constrained. Among the viral signals we detected an endogenous mavirus virophage potentially integrated within the nuclear genome of two distant uncultured stramenopiles. Virophages have been previously reported as a cell's defence mechanism against other viruses, and may therefore play an important ecological role in regulating protist populations. Our results point to single‐cell genomics as a powerful tool to investigate viral associations in uncultured protists, suggesting a wide distribution of these relationships, and providing new insights into the global viral diversity.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Chemical Characterization and Biotechnological Applicability of Pigments Isolated from Antarctic Bacteria - Tiago R. Silva; Renata S. N. Tavares; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Iramaia A. Neri-Numa; Glaucia M. Pastore; Luiz H. Rosa; José A. A. Schultz; Hosana M. Debonsi; Lorena R. G. Cordeiro; Valeria M. Oliveira (Marine Biotechnology, 2019)

Pigments in an iridescent bacterium, Cellulophaga fucicola, isolated from Antarctica - Tiago R. Silva; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Fábio N. dos Santos; Marcos N. Eberlin; Iramaia A. Neri-Numa; Glaucia M. Pastore; Renata S. N. Tavares; Hosana M. Debonsi; Lorena R. G. Cordeiro; Luiz H. Rosa; et al. (Antonie van Leeuwenhoek, 2019)

Quantifying long‐term recurrence in planktonic microbial eukaryotes - Caterina R. Giner; Vanessa Balagué; Anders K. Krabberød; Isabel Ferrera; Albert Reñé; Esther Garcés; Josep M. Gasol; Ramiro Logares; Ramon Massana (Molecular Ecology, 2019)
How much temporal recurrence is present in microbial assemblages is still an unanswered ecological question. Even though marked seasonal changes have been reported for whole microbial communities, less is known on the dynamics and seasonality of individual taxa. Here, we aim at understanding microbial recurrence at three different levels: community, taxonomic group and operational taxonomic units (OTUs). For that, we focused on a model microbial eukaryotic community populating a long‐term marine microbial observatory using 18S rRNA gene data from two organismal size fractions: the picoplankton (0.2–3 µm) and the nanoplankton (3–20 µm). We have developed an index to quantify recurrence in particular taxa. We found that community structure oscillated systematically between two main configurations corresponding to winter and summer over the 10 years studied. A few taxonomic groups such as Mamiellophyceae or MALV‐III presented clear recurrence (i.e., seasonality), whereas 13%–19% of the OTUs in both size fractions, accounting for ~40% of the relative abundance, featured recurrent dynamics. Altogether, our work links long‐term whole community dynamics with that of individual OTUs and taxonomic groups, indicating that recurrent and non‐recurrent changes characterize the dynamics of microbial assemblages.

Population connectivity of the plating coral Agaricia lamarcki from southwest Puerto Rico - Nicholas M. Hammerman; Ramon E. Rivera-Vicens; Matthew P. Galaska; Ernesto Weil; Richard S. Appledoorn; Monica Alfaro; Nikolaos V. Schizas (Coral Reefs, 2018)

Amazon Sailfin Catfish Pterygoplichthys pardalis (Loricariidae) in Bangladesh: A Critical Review of Its Invasive Threat to Native and Endemic Aquatic Species - Mohammad Hossain; Robert Vadas; Ramon Ruiz-Carus; Shams M. Galib (Fishes, 2018)
The Amazon sailfin catfish Pterygoplichthys pardalis is native to the Amazon River basin. It has since expanded its range to North America, the Caribbean, and more recently to South Asia, as with some of its congeners. Our paper reviews recent data from Bangladesh, clarifies taxonomic identification, and examines the potential effects of P. pardalis and congeneric species on local aquatic ecosystems and elsewhere in South Asia. Range expansions there probably reflect aquarium releases and escapes from aquaculture farms, as exacerbated by dispersal due to storm flooding and in impacted waters like irrigation canals. Given their potential ecosystem-level effects, we also review potential control mechanisms and human use for these invasive loricariids.

Contrasting evolutionary patterns in populations of demersal sharks throughout the western Mediterranean - Sergio Ramírez-Amaro; Antonia Picornell; Miguel Arenas; Jose A. Castro; Enric Massutí; M. M. Ramon; Bàrbara Terrasa (Marine Biology, 2018)

Shallow-level differentiation of phonolitic lavas from Sumaco Volcano, Ecuador - Jennifer M. Garrison; Kenneth W. W. Sims; Gene M. Yogodzinski; Ricardo D. Escobar; Sean Scott; Patricia Mothes; Minard L. Hall; Patricio Ramon (Contributions to Mineralogy and Petrology, 2018)

Cryptic genetic divergence in Scolopsis taenioptera (Perciformes: Nemipteridae) in the western Pacific Ocean - Ryo Kakioka; Nozomu Muto; Hirohiko Takeshima; Arnold C. Gaje; Ramon S. Cruz; Ulysses B. Alama; Armi May T. Guzman; Rex Ferdinand M. Traifalgar; Ricardo P. Babaran; Osman Muda; Wahidah Mohd Arshaad; Sukchai Arnupapboon; et al. (Ichthyological Research, 2018)

Temperature regulation of marine heterotrophic prokaryotes increases latitudinally as a breach between bottom‐up and top‐down controls - Xosé Anxelu G. Morán; Josep M. Gasol; Massimo C. Pernice; Jean‐François Mangot; Ramon Massana; Elena Lara; Dolors Vaqué; Carlos M. Duarte (Global Change Biology, 2017)
Planktonic heterotrophic prokaryotes make up the largest living biomass and process most organic matter in the ocean. Determining when and where the biomass and activity of heterotrophic prokaryotes are controlled by resource availability (bottom‐up), predation and viral lysis (top‐down) or temperature will help in future carbon cycling predictions. We conducted an extensive survey across subtropical and tropical waters of the Atlantic, Indian and Pacific Oceans during the Malaspina 2010 Global Circumnavigation Expedition and assessed indices for these three types of controls at 109 stations (mostly from the surface to 4,000 m depth). Temperature control was approached by the apparent activation energy in eV (ranging from 0.46 to 3.41), bottom‐up control by the slope of the log‐log relationship between biomass and production rate (ranging from −0.12 to 1.09) and top‐down control by an index that considers the relative abundances of heterotrophic nanoflagellates and viruses (ranging from 0.82 to 4.83). We conclude that temperature becomes dominant (i.e. activation energy >1.5 eV ) within a narrow window of intermediate values of bottom‐up (0.3–0.6) and top‐down 0.8–1.2) controls. A pervasive latitudinal pattern of decreasing temperature regulation towards the Equator, regardless of the oceanic basin, suggests that the impact of global warming on marine microbes and their biogeochemical function will be more intense at higher latitudes. Our analysis predicts that 1°C ocean warming will result in increased biomass of heterotrophic prokaryoplankton only in waters with

Seedling emergence through soil surface seals under laboratory conditions: effect of mechanical impedance and seal moisture - M. Teresa Mas; Antoni M. C. Verdú; Marta Ginovart; Ramon Josa (Biologia, 2017)

New morphological and molecular evidence confirm the presence of the Norwegian skate Dipturus nidarosiensis (Storm, 1881) in the Mediterranean Sea and extend its distribution to the western basin - S. RAMÍREZ-AMARO; F. ORDINES; M. ÁNGEL PUERTO; C. GARCÍA; C. RAMON; B. TERRASA; E. MASSUTÍ (Mediterranean Marine Science, 2017)
The present study confirms the presence of the Norwegian skate Dipturus nidarosiensis (Storm, 1881) in the Mediterranean Sea, by means of morphological traits and molecular markers providing the first record of this species in the Alboran Sea. Cannas et al. (2010) reported D. nidarosiensis for the first time in the Mediterranean from specimens captured in the central western basin, but Ebert & Stehmann (2013) and Stehmann et al. (2015) considered these records "likely refer to the smaller morphotype, Dipturus sp.", a species not yet described. Eight specimens of the Dipturus genus (Rajiformes: Rajidae) were caught off the Alboran Island (western Mediterranean) in 2012, 2013 and 2016, between 620 and 819 m depth. These specimens showed morphometric diagnostic features corresponding to those of Norwegian skates from the Northeast Atlantic and the central western Mediterranean Sea. Moreover, the Alboran individuals were genetically compared to Northeast Atlantic specimens available in GenBank by means of two mitochondrial DNA fragments: cytochrome c oxidase subunit I (COI) and cytochrome b (Cytb). Analyses showed that the Northeast Atlantic Norwegian skate specimens and the Alboran Sea ones were genetically similar and shared haplotypes, corroborating the identification of the Alboran individuals as Dipturus nidarosiensis. However, they were different from other Dipturus species distributed throughout the Northeast Atlantic and the Mediterranean Sea. Our results confirm the occurrence of this deep-sea large skate species in the Mediterranean, although the IUCN Red List of Threatened Species does not consider it possible (Stehmann et al., 2015).

Rapid and cost-effective molecular identification of the three mackerel species of the genus Rastrelliger (Perciformes: Scombridae) using PCR-RFLP analysis - Nozomu Muto; Hirohiko Takeshima; Ryo Kakioka; Ulysses B. Alama; Armi May T. Guzman; Ramon S. Cruz; Arnold C. Gaje; Rex Ferdinand M. Traifalgar; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; Satoshi Ishikawa (Marine Biodiversity, 2017)

Chemical defences of native European coccinellid eggs against intraguild predation by the invasive Asian coccinellid, Harmonia axyridis (Pallas) - A. Katsanis; A. Magro; F. Ramon-Portugal; M. Kenis; D. Babendreier (BioControl, 2017)

Attentional function and basal forebrain cholinergic neuron morphology during aging in the Ts65Dn mouse model of Down syndrome - Brian E. Powers; Ramon Velazquez; Christy M. Kelley; Jessica A. Ash; Myla S. Strawderman; Melissa J. Alldred; Stephen D. Ginsberg; Elliott J. Mufson; Barbara J. Strupp (Brain Structure and Function, 2016)

Microbial eukaryote communities exhibit robust biogeographical patterns along a gradient of Patagonian and Antarctic lakes - M. Romina Schiaffino; Enrique Lara; Leonardo D. Fernández; Vanessa Balagué; David Singer; Christophe C. W. Seppey; Ramon Massana; Irina Izaguirre (Environmental Microbiology, 2016)
Summary Microbial eukaryotes play important roles in aquatic ecosystem functioning. Unravelling their distribution patterns and biogeography provides important baseline information to infer the underlying mechanisms that regulate the biodiversity and complexity of ecosystems. We studied the distribution patterns and factors driving diversity gradients in microeukaryote communities (total, abundant, uncommon and rare community composition) along a latitudinal gradient of lakes distributed from Argentinean Patagonia to Maritime Antarctica using both denaturing gradient gel electrophoresis (DGGE) and high‐throughput sequencing (Illumina HiSeq). DGGE and abundant Illumina operational taxonomic units (OTUs) showed both decreasing richness with latitude and significant differences between Patagonian and Antarctic lakes communities. In contrast, total richness did not change significantly across the latitudinal gradient, although evenness and diversity indices were significantly higher in Patagonian lakes. Beta‐diversity was characterized by a high species turnover, influenced by both environmental and geographical descriptors, although this pattern faded in the rare community. Our results suggest the co‐existence of a ‘core biosphere’ containing reduced number of abundant/dominant OTUs on which classical ecological rules apply, together with a much larger seedbank of rare OTUs driven by stochastic and reduced dispersal processes. These findings shed new light on the biogeographical patterns and forces structuring inland microeukaryote composition across broad spatial scales.

Hydrological soil behavior in areas with semi-arid vegetation (Beni Chougrane Mountains, Algeria) - Yahia Boukhari; Marta Ginovart; Antoni M. C. Verdú; M. Teresa Mas; Khalladi Mederbal; Ramon Josa (Biologia, 2016)

Evaluation of Alternative High-Throughput Sequencing Methodologies for the Monitoring of Marine Picoplanktonic Biodiversity Based on rRNA Gene Amplicons - Isabel Ferrera; Caterina R. Giner; Albert Reñé; Jordi Camp; Ramon Massana; Josep M. Gasol; Esther Garcés (Frontiers in Marine Science, 2016)

Vertical distribution of major photosynthetic picoeukaryotic groups in stratified marine waters - Ana M. Cabello; Mikel Latasa; Irene Forn; Xosé Anxelu G. Morán; Ramon Massana (Environmental Microbiology, 2016)
Summary Photosynthetic picoeukaryotes (PPEs) are fundamental contributors to oceanic primary production and form diverse communities dominated by prymnesiophytes, chlorophytes, pelagophytes and chrysophytes. Here, we studied the vertical distribution of these major groups in two offshore regions of the northern Iberian Peninsula during summer stratification. We performed a fine‐scale vertical sampling (every ∼2 m) across the DCM and used fluorescence in situ hybridization (FISH) to determine the PPE composition and to explore the possible segregation of target groups in the light, nutrient and temperature gradients. Chlorophytes, pelagophytes and prymnesiophytes, in this order of abundance, accounted for the total PPEs recorded by flow cytometry in the Avilés canyon, and for more than half in the Galicia Bank, whereas chrysophytes were undetected. Among the three detected groups, often the prymnesiophytes were dominant in biomass. In general, all groups were present throughout the water column with abundance peaks around the DCM, but their distributions differed: pelagophytes were located deeper than the other two groups, chlorophytes presented two peaks and prymnesiophytes exhibited surface abundances comparable to those at the DCM. This study offers first indications that the vertical distribution of different PPE groups is heterogeneous within the DCM.

Genetic and morphological differences among the three species of the genus Rastrelliger (Perciformes: Scombridae) - Nozomu Muto; Ulysses B. Alama; Harutaka Hata; Armi May T. Guzman; Ramon Cruz; Arnold Gaje; Rex Ferdinand M. Traifalgar; Ryo Kakioka; Hirohiko Takeshima; Hiroyuki Motomura; Fumihito Muto; Ricardo P. Babaran; et al. (Ichthyological Research, 2016)

Postmortem Biochemical and Microbiological Changes in Loricariid Catfish ( Pterygoplichthys disjunctivus) Muscle During Ice Storage - Enrique Marquez-Rios; Ramon Pacheco-Aguilar; Juan Carlos Ramirez-Suarez; Victor M. Ocano-Higuera; Celia O. García-Sifuentes; Susana M. Scheuren-Acevedo; Miguel A. Mazorra-Manzano (Journal of Aquatic Food Product Technology, 2016)

Differential Gene Expression in Liver, Gill, and Olfactory Rosettes of Coho Salmon (Oncorhynchus kisutch) After Acclimation to Salinity - Lindley A. Maryoung; Ramon Lavado; Theo K. Bammler; Evan P. Gallagher; Patricia L. Stapleton; Richard P. Beyer; Federico M. Farin; Gary Hardiman; Daniel Schlenk (Marine Biotechnology, 2015)

Identifiability of PBPK models with applications to dimethylarsinic acid exposure - Ramon I. Garcia; Joseph G. Ibrahim; John F. Wambaugh; Elaina M. Kenyon; R. Woodrow Setzer (Journal of Pharmacokinetics and Pharmacodynamics, 2015)

Effect of Simultaneous Administration of Dihydroxyacetone on the Diffusion of Lawsone Through Various In Vitro Skin Models - Daniel J. Munt; Anne Grana; Martin Hulce; Ramon M. Fusaro; Alekha K. Dash (AAPS PharmSciTech, 2015)

A novel approach to teaching pharmacotherapeutics—feasibility of the learner-centered student-run clinic - Ramon S. Dekker; Tim Schutte; Jelle Tichelaar; Abel Thijs; Michiel A. van Agtmael; Theo P. G. M. de Vries; Milan C. Richir (European Journal of Clinical Pharmacology, 2015)

Hardpan in skeletal soils: Statistical approach to determine its depth in a cherry orchard plot - Ramon Josa; Marta Ginovart; Maria Teresa Mas; Antoni M. C. Verdú (Biologia, 2015)

Development of the Global Earthquake Model’s neotectonic fault database - Annemarie Christophersen; Nicola Litchfield; Kelvin Berryman; Richard Thomas; Roberto Basili; Laura Wallace; William Ries; Gavin P. Hayes; Kathleen M. Haller; Toshikazu Yoshioka; Richard D. Koehler; Dan Clark; et al. (Natural Hazards, 2015)

Trace element fluxes in sediments of an environmentally impacted river from a coastal zone of Brazil - Yuri Jacques Agra Bezerra da Silva; José Ramon Barros Cantalice; Vijay P. Singh; Clístenes Williams Araújo do Nascimento; Victor Casimiro Piscoya; Sérgio M. S. Guerra (Environmental Science and Pollution Research, 2015)

Assessing the Energetic and Environmental Impacts of the Operation and Maintenance of Spanish Sewer Networks from a Life-Cycle Perspective - Anna Petit-Boix; David Sanjuan-Delmás; Sergio Chenel; Desirée Marín; Carles M. Gasol; Ramon Farreny; Gara Villalba; María Eugenia Suárez-Ojeda; Xavier Gabarrell; Alejandro Josa; Joan Rieradevall (Water Resources Management, 2015)

Anti-inflammatory activity in selected Antarctic benthic organisms - Juan Moles; Anna Torrent; M. José Alcaraz; Ramon RuhÃ; Conxita Avila (Frontiers in Marine Science, 2014)

Relationship between bedload and suspended sediment in the sand-bed Exu River, in the semi-arid region of Brazil - Jose Ramon B. Cantalice; Moacyr Cunha Filho; Borko D. Stosic; Victor Casimiro Piscoya; Sergio M. S. Guerra; Vijay P. Singh (Hydrological Sciences Journal, 2013)

Multilocus genetic diversity and historical biogeography of the endemic wall lizard from I biza and F ormentera, P odarcis pityusensis ( S quamata: L acertidae) - V. Rodríguez; R. P. Brown; B. Terrasa; V. Pérez‐Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Molecular Ecology, 2013)
Two monophyletic sister species of wall lizards inhabit the two main groups of B alearic I slands: P odarcis lilfordi from islets and small islands around M allorca and M enorca and P odarcis pityusensis from I biza, F ormentera and associated islets. Genetic diversity within the endangered P . lilfordi has been well characterized, but P . pityusensis has not been studied in depth. Here, 2430 bp of mt DNA and 15 microsatellite loci were analysed from P . pityusensis populations from across its natural range. Two main genetic groupings were identified, although geographical structuring differed slightly between the mt DNA and the nuclear loci. In general, individuals from islets/islands adjacent to the main island of I biza were genetically distinct from those from F ormentera and the associated F reus islands for both mt DNA and the nuclear loci. However, most individuals from the island of I biza were grouped with neighbouring islets/islands for nuclear loci, but with F ormentera and F reus islands for the mitochondrial locus. A time‐calibrated B ayesian tree was constructed for the principal mitochondrial lineages within the B alearics, using the multispecies coalescent model, and provided statistical support for divergence of the two main P . pityusensis lineages 0.111–0.295 Ma. This suggests a mid‐late P leistocene intraspecific divergence, compared with an early P leistocene divergence in P . lilfordi , and postdates some major increases in sea level between 0.4 and 0.6 Ma, which may have flooded F ormentera. The program IM a2 provided a posterior divergence time of 0.089–0.221 Ma, which was similar to the multispecies coalescent tree estimate. More significantly, it indicated low but asymmetric effective gene copy migration rates, with higher migration from F ormentera to I biza populations. Our findings suggest that much of the present‐day diversity may have originated from a late P leistocene colonization of one island group from the other, followed by allopatric divergence of these populations. Subsequent gene flow between these insular groups seems likely to be explained by recent human introductions. Two evolutionary significant units can be defined for P . pityusensis but these units would need to exclude the populations that have been the subjects of recent admixture.

Fermentation of glycerol and production of valuable chemical and biofuel molecules - Anu Jose Mattam; James M. Clomburg; Ramon Gonzalez; Syed Shams Yazdani (Biotechnology Letters, 2013)

Modelling the Ecological Vulnerability to Forest Fires in Mediterranean Ecosystems Using Geographic Information Technologies - Beatriz Duguy; José Antonio Alloza; M. Jaime Baeza; Juan De la Riva; Maite Echeverría; Paloma Ibarra; Juan Llovet; Fernando Pérez Cabello; Pere Rovira; Ramon V. Vallejo (Environmental Management, 2012)

Cinnamtannin B-1, a natural antioxidant that reduces the effects of H2O2 on CCK-8-evoked responses in mouse pancreatic acinar cells - Antonio Gonzalez; Patricia Santofimia-Castaño; Ramon Rivera-Barreno; Gines M. Salido (Journal of Physiology and Biochemistry, 2012)

Numerical Study of the Neutral Atmospheric Boundary Layer Over Complex Terrain - Gilberto A. A. Moreira; André A. C. dos Santos; Carlos A. M. do Nascimento; Ramon M. Valle (Boundary-Layer Meteorology, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

Environmental analysis of rainwater harvesting infrastructures in diffuse and compact urban models of Mediterranean climate - Sara Angrill; Ramon Farreny; Carles M. Gasol; Xavier Gabarrell; Bernat Viñolas; Alejandro Josa; Joan Rieradevall (The International Journal of Life Cycle Assessment, 2012)

Diel changes in bulk and single‐cell bacterial heterotrophic activity in winter surface waters of the northwestern Mediterranean Sea - Clara Ruiz-González; Thomas Lefort; Ramon Massana; Rafel Simó; Josep M. Gasol (Limnology and Oceanography, 2012)
Two diel cycle studies were conducted to determine the effect of day—night light changes on winter bacterial activity in the coastal Mediterranean (Blanes Bay Microbial Observatory). Bacterial abundances, bacterial heterotrophic activity, and flagellate grazing counts were determined at 4‐h intervals during two 3‐d periods separated by 2 d. Twice a day, the single‐cell activity of major bacterial groups was further analyzed by applying microautoradiography combined with catalyzed reporter deposition—fluorescence in situ hybridization. During the first cycle, all the measured parameters (including the number of active cells in most groups) varied synchronously, with higher values at night and lower during the day. An episode of strong winds between the two studied periods disrupted this periodicity at the onset of the second cycle. The bulk incorporation of 3 H‐leucine recovered the diel pattern after 2 d, mostly driven by the activity of Gammaproteobacteria. Among the possibilities considered, the observed nighttime increases in the grazing activity of heterotrophic nanoflagellates appeared to partially drive the activity of all bacterial taxa through potential periodic release of dissolved organic matter.

Synthesis and in vitro inhibition properties of siRNA conjugates carrying glucose and galactose with different presentations - Anna Aviñó; Sandra M. Ocampo; Ricardo Lucas; José J. Reina; Juan Carlos Morales; José Carlos Perales; Ramon Eritja (Molecular Diversity, 2011)

Reconstruction of annual winter rainfall since A.D.1579 in central-eastern Spain based on calcite laminated sediment from Lake La Cruz - Lidia Romero-Viana; Ramon Julià; Martin Schimmel; Antonio Camacho; Eduardo Vicente; M. Rosa Miracle (Climatic Change, 2011)

Polymorphic microsatellite loci for the Balearic Island Lizard Podarcis lilfordi (Squamata: Lacertidae) - P. Bloor; V. Rodríguez; B. Terrasa; R. P. Brown; V. Pérez-Mellado; J. A. Castro; A. Picornell; M. M. Ramon (Conservation Genetics Resources, 2011)

Identification of a potent activator of Akt phosphorylation from a novel series of phenolic, picolinic, pyridino, and hydroxamic zinc(II) complexes - Savvas N. Georgiades; Lok Hang Mak; Inmaculada Angurell; Evelyn Rosivatz; M. Firouz Mohd Mustapa; Christoulla Polychroni; Rudiger Woscholski; Ramon Vilar (JBIC Journal of Biological Inorganic Chemistry, 2011)

The effects of winter severity and population density on body stores in the Iberian wild goat (Capra pyrenaica) in a highly seasonal mountain environment - Emmanuel Serrano; Jose Enrique Granados; Mathieu Sarasa; Francisco Jose González; Paulino Fandos; Ramon C. Soriguer; Jesus M. Pérez (European Journal of Wildlife Research, 2011)

Modelling the Effect of Tree Foliage on Sprayer Airflow in Orchards - Ayenew Melese Endalew; Christof Debaer; Nick Rutten; Jef Vercammen; Mulugeta Admasu Delele; Herman Ramon; Bart M. Nicolaï; Pieter Verboven (Boundary-Layer Meteorology, 2011)

Inter‐annual recurrence of archaeal assemblages in the coastal NW Mediterranean Sea (Blanes Bay Microbial Observatory) - Pierre E. Galand; Carmen Gutiérrez-Provecho; Ramon Massana; Josep M. Gasol; Emilio O. Casamayor (Limnology and Oceanography, 2010)
We report a long‐term (i.e., 4.5 consecutive yr) monitoring of surface marine archaeal assemblages of the coastal Mediterranean Sea using quantitative polymerase chain reaction against specific phylogenetic and functional genes, and, for some specific samples, clone libraries of the 16S ribosomal ribonucleic acid gene. Archaea had a marked seasonal periodicity, with recurrent peaks of abundance in December and January and very low occurrence during summer, parallel to temporal changes in community composition. Group II.b Euryarchaeota sequences were mostly present during winter when water was nutrient‐enriched, and phytoplankton were abundant. Group II.a sequences were, in turn, more abundant during summer when the water column is stratified, and nutrient concentrations and phytoplankton stocks were lower. Group I Crenarchaeota abundance was highest during winter and significantly correlated with that of archaeal ammonia monooxygenase ( amoA ) gene copies and nitrite concentrations, suggesting that Group I Crenarchaeota were ammonia oxidizers. The periodicity of archaeal assemblages matched the strong and predictable seasonality of the surface‐water conditions in the northwestern Mediterranean Sea, and suggests a low degree of functional redundancy between archaeal groups. The distinct seasonal dynamics for Group II.a and II.b Euryarchaeota , and their close association with major ecosystem processes, indicate that they may play an important but as yet largely unknown role in the ocean.

Effect of the presence of the plant growth promoting rhizobacterium (PGPR) Chryseobacterium balustinum Aur9 and salt stress in the pattern of flavonoids exuded by soybean roots - Marta S. Dardanelli; Hamid Manyani; Sergio González-Barroso; Miguel A. Rodríguez-Carvajal; Antonio M. Gil-Serrano; Maria R. Espuny; Francisco Javier López-Baena; Ramon A. Bellogín; Manuel Megías; Francisco J. Ollero (Plant and Soil, 2010)

Nicotine-conditioned place preference induced CREB phosphorylation and Fos expression in the adult rat brain - Mariano M. Pascual; Veronica Pastor; Ramon O. Bernabeu (Psychopharmacology, 2009)

Stepwise synthesis of RNA conjugates carrying peptide sequences for RNA interference studies - Anna Aviñó; Sandra M. Ocampo; Clara Caminal; José Carlos Perales; Ramon Eritja (Molecular Diversity, 2009)

Setting the record straight: a rebuttal to an erroneous analysis on transgenic insecticidal crops and natural enemies - Anthony M. Shelton; Steven E. Naranjo; Jörg Romeis; Richard L. Hellmich; Jeffrey D. Wolt; Brian A. Federici; Ramon Albajes; Franz Bigler; Elisabeth P. J. Burgess; Galen P. Dively; Angharad M. R. Gatehouse; Louise A. Malone; et al. (Transgenic Research, 2009)

Prevalence of BRCA1 and BRCA2 mutations in breast cancer patients from Cuba - Rolando Comacho Rodriguez; Antonio Alejandro Esperon; Ramon Ropero; Maria Caridad Rubio; Ronald Rodriguez; Rosa M. Ortiz; Juan J. Lence Anta; Mario de los Rios; Deyanira Carnesolta; Maria C. del Olivera; Somalia Stiu Vansam; Robert Royer; et al. (Familial Cancer, 2008)

Life cycle assessment comparison among different reuse intensities for industrial wooden containers - Carles M. Gasol; Ramon Farreny; Xavier Gabarrell; Joan Rieradevall (The International Journal of Life Cycle Assessment, 2008)

Factors Controlling the Year-Round Variability in Carbon Flux Through Bacteria in a Coastal Marine System - Laura Alonso-Sáez; Evaristo Vázquez-Domínguez; Clara Cardelús; Jarone Pinhassi; M. Montserrat Sala; Itziar Lekunberri; Vanessa Balagué; Maria Vila-Costa; Fernando Unrein; Ramon Massana; Rafel Simó; Josep M. Gasol (Ecosystems, 2008)

Pancreatic cancer and the FAMMM syndrome - Henry T. Lynch; Ramon M. Fusaro; Jane F. Lynch; Randall Brand (Familial Cancer, 2008)

ABI4 mediates the effects of exogenous trehalose on Arabidopsis growth and starch breakdown - Matthew Ramon; Filip Rolland; Johan M. Thevelein; Patrick Van Dijck; Barbara Leyman (Plant Molecular Biology, 2007)

Significant year‐round effect of small mixotrophic flagellates on bacterioplankton in an oligotrophic coastal system - Fernando Unrein; Ramon Massana; Laura Alonso-Sáez; Josep M. Gasol (Limnology and Oceanography, 2007)
The seasonal variation in the grazing effect of mixotrophic flagellates on bacterioplankton was assessed during an annual cycle in an oligotrophic coastal station in the northwest Mediterranean Sea. Ingestion rates of fluorescently labeled bacteria were estimated for different size categories of phytoflagellates (PF) and heterotrophic flagellates (HF) in short‐term experiments and compared with long‐term grazing estimates and published empirical models. The mixotrophic flagellates included haptophyte‐like cells, cryptophytes, and dinoflagellates. The group‐specific grazing rates (SGR) averaged 1.1 (3–5 µm PF), 1.3 (5–20 µm PF), 4.0 ( −1 h −1 (5‐20 µm HF). Lower SGR but higher abundances of PF resulted in an average mixotroph contribution of 50% to the total flagellate grazing. Remarkably, the effect was relatively high all through the year (35–65%). Regardless of the presence of chloroplasts, flagellates

Seismogenic destruction of the Kamenka medieval fortress, northern Issyk-Kul region, Tien Shan (Kyrgyzstan) - Andrey M. Korjenkov; J. Ramon Arrowsmith; Christopher Crosby; Ernes Mamyrov; Lyubov A. Orlova; Irina E. Povolotskaya; Kubatbek Tabaldiev (Journal of Seismology, 2006)

Seasonal changes in chlorophyll distributions in Amazon floodplain lakes derived from MODIS images - Evlyn Márcia Leão de Moraes Novo; Cláudio Clemente de Farias Barbosa; Ramon Moraes de Freitas; Yosio Edimir Shimabukuro; John M. Melack; Waterloo Pereira Filho (Limnology, 2006)

Effects of exposure to ED contaminants (TPT-Cl and Fenarimol) on crinoid echinoderms: comparative analysis of regenerative development and correlated steroid levels - Alice Barbaglio; Daniela Mozzi; Michela Sugni; Paolo Tremolada; Francesco Bonasoro; Ramon Lavado; Cinta Porte; M. Daniela Candia Carnevali (Marine Biology, 2006)

Guest Editors' preface - M. Ramon Llamas; Aditi Mukherji; Tushaar Shah (Hydrogeology Journal, 2006)

Comment on the article “A participatory approach to integrated aquifer management: The case of Guanajuato state, Mexico” By R. Sandoval (H. J. February, 2004) - M. Ramon Llamas (Hydrogeology Journal, 2006)

Quantitative assessment of the residual risk in a rockfall protected area - Jordi Corominas; Ramon Copons; José Moya; Joan M. Vilaplana; Joan Altimir; Jordi Amigó (Landslides, 2005)

Spatial Variations of Local Magnitude in Earthquakes Recorded in Northeastern Spain - Josep Vila; Ramon Macià; Antoni M. Correig (Pure and Applied Geophysics, 2005)

Role of Soft Bone, CSF and Gray Matter in EEG Simulations - Ceon Ramon; P. Schimpf; J. Haueisen; M. Holmes; A. Ishimaru (Brain Topography, 2004)

Enhanced myogenic differentiation by extracellular matrix is regulated at the early stages of myogenesis - Ramon C. J. Langen; Anemie M. W. J. Schols; Marco C. J. M. Kelders; Emiel F. M. Wouters; Yvonne M. W. Janssen-Heininger (In Vitro Cellular & Developmental Biology - Animal, 2003)

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.

ENHANCED MYOGENIC DIFFERENTIATION BY EXTRACELLULAR MATRIX IS REGULATED AT THE EARLY STAGES OF MYOGENESIS - RAMON C. J. LANGEN; ANNEMIE M. W. J. SCHOLS; MARCO C. J. M. KELDERS; EMIEL F. M. WOUTERS; YVONNE M. W. JANSSEN-HEININGER (In Vitro Cellular & Developmental Biology - Animal, 2003)

Introgression of resistance to late blight (Phytophthora infestans) from Solanum pinnatisectum into S. tuberosum using embryo rescue and double pollination - M. Ramon; R.E. Hanneman (Euphytica, 2002)

Synthesis of Pegylated Immunonanoparticles - Jean-Christophe Olivier; Ramon Huertas; Hwa Jeong Lee; Frederic Calon; William M. Pardridge (Pharmaceutical Research, 2002)

Changes in archaeal, bacterial and eukaryal assemblages along a salinity gradient by comparison of genetic fingerprinting methods in a multipond solar saltern - Emilio O. Casamayor; Ramon Massana; Susana Benlloch; Lise Øvreås; Beatriz Díez; Victoria J. Goddard; Josep M. Gasol; Ian Joint; Francisco Rodríguez‐Valera; Carlos Pedrós‐Alió (Environmental Microbiology, 2002)
Summary Microbial communities inhabiting a multipond solar saltern were analysed and compared using SSU rRNA polymerase chain reaction (PCR)‐based fingerprintings carried out in parallel by four laboratories. A salinity gradient from seawater (3.7%) to NaCl precipitation (37%) was studied for Bacteria, Archaea and Eukarya, and laboratories applied their own techniques and protocols on the same set of samples. Members of all three domains were retrieved from all salt concentrations. Three fingerprinting techniques were used: denaturing gradient gel electrophoresis (DGGE), ribosomal internal spacer analysis (RISA), and terminal‐restriction fragments length polymorphism (T‐RFLP). In addition, each laboratory used its own biomass collection method and DNA extraction protocols. Prokaryotes were addressed using DGGE and RISA with different ‘domain‐specific’ primers sets. Eukaryotes were analysed by one laboratory using DGGE and T‐RFLP, but targeting the same 18S rDNA site. Fingerprints were compared through cluster analysis and non‐metric multidimensional scaling plots. This exercise allowed fast comparison of microbial assemblages and determined to what extent the picture provided by each laboratory was similar to those of others. Formation of two main, salinity‐based groups of samples in prokaryotes (4–15% and 22–37% salinity) was consistent for all the laboratories. When other clusters appeared, this was a result of the particular technique and the protocol used in each case, but more affected by the primers set used. Eukaryotic microorganisms changed more from pond to pond; 4–5% and 8–37% salinity were but the two main groups detected. Archaea showed the lowest number of bands whereas Eukarya showed the highest number of operational taxonomic units (OTUs) in the initial ponds. Artefacts appeared in the DGGE from ponds with extremely low microbial richness. On the other hand, different 16S rDNA fragments with the same restriction or internal transcribed spacer (ITS) length were the main limitations for T‐RFLP and RISA analyses, respectively, in ponds with the highest OTUs richness. However, although the particular taxonomic composition could vary among protocols, the general structure of the microbial assemblages was maintained.

Planktonic chlorophyll a and eutrophication in two Mediterranean littoral systems (Mallorca Island, Spain) - M. Puigserver; G. Ramon; G. Moyà; A. Martínez-Taberner (Hydrobiologia, 2002)

Changes in marine bacterioplankton phylogenetic composition during incubations designed to measure biogeochemically significant parameters - Ramon Massana; Carlos PedrόsߚAliό; Emilio O. Casamayor; Josep M. Gasol (Limnology and Oceanography, 2001)
Bottle incubations, during which the activity and growth of prokaryotes is monitored during several days, are frequently carried out to study functional aspects of marine prokaryotic assemblages. These experiments will relate directly to in situ activities if all populations grow harmonically during the incubation. We tested whether this was the case by analyzing the composition of bacterial assemblages at the beginning and at the end of the incubation by denaturing gradient gel electrophoresis. Five experiments were done in different Antarctic regions. Bacterial assemblages north and south of the Polar Front were very different. In all cases, the final assemblages were very different from the initial ones, and these changes were often accompanied by a significant decrease of diversity indices. Our experiments included treatments with different temperature and organic matter amendments. Whereas the increase in temperature tested had a minor effect on prokaryotic growth rate and specific composition, the addition of organic matter strongly stimulated growth rate and selected a particular bacterial assemblage in some experiments but not in others. A significant component of bacterial assemblages from waters south of the Polar Front appeared to be Polaribacter franzmannii , a gas vacuolated bacterium of the CytophagaߚFlavobacteriumߚBacteroides group that was originally isolated from Antarctic sea ice. This phylotype was enriched and dominated in almost all final assemblages. Our results indicate that longߚterm bottle incubations mostly measure the activity of a few opportunistic bacteria and not that of the original assemblage. This should be taken into account if data obtained in these experiments are used for balancing whole ecosystem carbon budgets and to derive biogeochemical conclusions.

Dietary fat intake and prostate cancer risk: a case–control study in Spain - Josep M. Ramon; Ricard Bou; Soledad Romea; M. Eugenia Alkiza; Merce Jacas; Josefa Ribes; Joaquim Oromi (Cancer Causes & Control, 2000)

Role of the melanocortin-4 receptor in metabolic rate and food intake in mice - Airu S. Chen; Joseph M. Metzger; Myrna E. Trumbauer; Xiao-ming Guan; Hong Yu; Easter G. Frazier; Donald J. Marsh; Michael J. Forrest; Shobhna Gopal-Truter; Jill Fisher; Ramon E. Camacho; Alison M. Strack; et al. (Transgenic Research, 2000)

Regulation by members of the transforming growth factor beta superfamily of the digital and interdigital fates of the autopodial limb mesoderm - Domingo Macias; Yolanda Gañan; Joaquin Rodriguez-Leon; Ramon Merino; J. M. Hurle (Cell and Tissue Research, 1999)

Mixing of floodwaters in a restored habitat wetland in northeastern Ontario - Janice M. Gilbert; Barry G. Warner; Ramon Aravena; J. Chris Davies; Douglas Brook (Wetlands, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)